(untitled) (Research, Society and Development, 2024)
American cutaneous leishmaniasis (ATL) is an infectious disease with chronic evolution and vector transmission. It is the most prevalent form of leishmaniasis, being directly related to poverty and generating significant social impact. Considering its occurrence in the Northeast of Brazil, the objective here was to carry out an epidemiological characterization, analysis of the incidence and trend of ATL in twenty years. The processed data were obtained from the Information Technology Department of the Unified Health System (DATASUS) of the Ministry of Health, and for temporal trend analysis, joinpoint regression models (segmented linear regression) were used. In total, 141,140 cases of ATL were reported, with Bahia, Maranhão and Ceará being the states with the highest notifications. The results obtained showed that there was a decrease in cases throughout the study period. The predominant epidemiological characteristics were: male sex (62.44%), age group from 20 to 39 years old (34.57%) and brown ethnicity (56.15%). In the clinical form, cutaneous leishmaniasis was predominant (94.51%), 91.77% were new cases and 78.34% were autochthonous cases. In the temporal trend analysis, Bahia grew between 2004 and 2010 (APC= 17.8*; p-value 0.014). From 2011 onwards, the patterns were declining in most states, only Alagoas, Paraíba and Rio Grande do Norte had no changes in numbers, remaining stationary for the period. The study allows us to understand the dynamics of ATL in the region and contribute to health systems at regional and state levels for effective surveillance and control.